Indícios de Burnout em profissionais das estratégias de saúde da família de uruguaiana/RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
resumo em inglês Detect evidence of burnout in health professionals working in the esf’s uruguaiana-rs and verify the need to implement policies preventive measures. methods: descriptive, prospective, quantitative and cross-sectional study transversal with the health professionals inserted in the 17 esf’s in the municipality of uruguaiana - rs in 2019. participants answered the chafic questionnaire jbeili inspired by the maslach burnout inventory containing 20 questions with answers staggered closed. from this, they were classified among one of the five scoring possibilities attributed: no evidence of burnout, possibility of develop burnout, initial phase, beginning of installation and considerable phase of syndrome. results: of the 181 working professionals, only 100 participated in the survey (55%). evidence of burnout was observed in 52% of the participants, while 45% had the possibility of developing the syndrome and only 3% did not showed no evidence. highest scores were between 41 and 60 indicating the initial phase of burnout, recommending the search for a professional to eliminate symptoms, guaranteeing quality of life and professional performance. conclusions: evidence of burnout was detected in 52% of health professionals active in the esf’s in uruguaiana - rs who participated in the research, demonstrating the need to implement policies that assist in their prevention.
Burnout indications in professionals of the family health strategies of Uruguaiana/RS
Keywords: Work; Síndrome de Burnout; Saúde do trabalhador; Profissional da saúde; Uruguaiana; Saúde pública; Medicina Veterinária; Anestesiologia Veterinária; Health professional; Public health; Burnout syndrome; Saúde da família; CNPQ::CIENCIAS AGRARIAS